Prevalence of resistance mechanisms against macrolides and lincosamides in methicillin-resistant coagulase-negative staphylococci in the Czech Republic and occurrence of an undefined mechanism of resistance to lincosamides - Novotna, Gabriela; Adamkova, Václava; Janata, Jiri; Melter, Oto; Spizek, Jaroslav (Antimicrobial agents and chemotherapy, 2005)
High occurrence of the non-macrolide-lincosamide-streptogramin B resistance genes msrA (53%) and linA/linA' (30%) was found among 98 methicillin-resistant coagulase-negative staphylococci additionally resistant to macrolides and/or lincosamides. The gene msrA predominated in Staphylococcus haemolyticus (43 of 62 isolates). In Staphylococcus epidermidis, it was present in 7 of 27 isolates. A novel mechanism of resistance to lincosamides appears to be present in 10 genetically related isolates of S. haemolyticus in the absence of ermA, ermC, msrA, and linA/linA'.
Keywords: Bacterial Proteins; rezistence na methicilin; Česká republika; Drug Resistance, Bacterial; antibakteriální látky; membránové transportní proteiny; Microbial Sensitivity Tests; Methicillin Resistance; koagulasa; incidence; Lincosamides; Staphylococcus; Membrane Transport Proteins; Coagulase; Czech Republic; lidé; Anti-Bacterial Agents; Humans; bakteriální léková rezistence; mikrobiální testy citlivosti; bakteriální proteiny; Macrolides; makrolidy; Incidence; linkosamidy